When sustainability of a tourism destination is a requirement: Does the consumer perceive sacrifices in diving experiences? - Polyanna de Lourdes Saraiva do Nascimento; Salomão Alencar de Farias (Journal of Spatial and Organizational Dynamics, 2017)
Consumer behaviour refers to some subjective characteristics of individuals, their cultural principles and living experiences throughout their lives, aspects that awaken the individual’s desire to consume certain products and services and sometimes the tendency to give up some personal and discretionary resources to concretize this consumption, in other words, to make sacrifices. In this present study, the emphasis focuses on the understanding of the way Dutch and Brazilian consumers carry out the sacrifice in diving experiences, while the practice of sustainability is required. Therefore, the aspects that motivated this study are related to the need to explore the sacrifice theme in consumer relations, mainly when associated with products and services where the hedonic experience is felt, as it is through diving. The research is interpretative, considering that it captures objective results from the studied phenomenon, by using semi-structured interviews collected with divers, totalling twenty-three interviews in Brazil and Netherlands. The collected data was analysed according to content analysis. The results pointed out the relationship between sacrifices and sustainability, in diving experiences associated with the abdication of resources such as: recreation, time, comfort and money. Moreover, the predisposition to sacrifice something is directly related to living experiences during the practice of the activity, considering that it awakens positive feelings and generates a strong individual affective commitment. These aspects emphasize the provision of the individuals to follow the rules for sustainability determined by tourist destinations for diving, as well as the desire to explore without destroying, aiming to keep practicing that activity are that location.